ÉTUDE SPATIALE ET TEMPORELLE DE LA SALINITE DANS LES SOLS DE LA PLAINE DE MINA (RELIZANE) - GACEM Farid (My University, 2015)
Control soil salinity, with the knowledge of the spatial distribution and its evolution over time, it becomes necessary to lead to strategies sustainable agricultural development. The conventional method for determining the salinity by measuring the electrical conductivity of an extract of the saturated soil (ECe) dough remains difficult because of the large spatial variability of salt levels from one point to another which makes this laborious method. As an alternative, the electromagnetic induction unit (EM38), was developed by Geonics Ltd. (Canada) and can be used to facilitate the swift action of soil salinity in the field. It is fast and allows a high density of measurement points. The present work aims to study the spatio- temporal evolution of soil salinity, by using this method on a plot cultivated representative of the plain of Mina (Relizane). A set of 9090 measurements of electromagnetic conductivity (ECM) were performed on a regular grid of 10 × 10 m with the EM38 instrument, while 160 samples were taken for determination of stocks. Of multiple linear regression models were used to convert the values of ECM stocks. Kriging was used to extrapolate to unsampled locations. The development of salinity maps was based on the predicted values. The results showed cycles of salinization and soil desalinization. Saline profiles are top-down with saline peaks reflecting a transfer of salts and their redistribution. Three soil profiles were implanted at the study plot, and underwent a detailed morphological description and physical and chemical analyzes were determined in the laboratory. The profiles were then classified in the American classification system (Soil Taxonomy).
Keywords: Salinity, Electric conductivity, Electromagnetic conductivity, Krigeage, Mina